PENGARUH LATIHAN VARIASI SERVIS TERHADAP AKURASI SERVIS ATAS PADA PERMAINAN BOLA VOLI - Ikaldung Boangmanalu; Khaidir Hamsah; Jona Fancisco Sihotang; Ahmad Yasir Arafat; Jun Steven Ginting; M. Ishak; Rahmi Aulia (STKIP Subang, 2026)
This study aimed to determine the effect of service variation training on the accuracy of overhand service in volleyball games. The research method used was a quasi-experimental method with a One Group Pretest-Posttest Design. The research sample consisted of volleyball extracurricular participants selected using purposive sampling techniques. The research instrument used was an overhand service accuracy test in volleyball. Data collection techniques were carried out through pretests and posttests, while data analysis used the t-test. The results showed that there was an improvement in overhand service ability after being given treatment in the form of service variation training. Based on the hypothesis test results, the value of was greater than at a significance level of 5%, so the research hypothesis was accepted. These results indicate that service variation training has a significant effect on the accuracy of overhand service in volleyball games. Therefore, service variation training can be used as an effective training method to improve basic overhand service skills.